2021
DOI: 10.21203/rs.3.rs-613222/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying The Most Important Workplace Factors in Predicting Mental Health Among British Columbia Nurses Using Machine Learning Techniques

Abstract: Objectives Nurses are at a high risk of developing mental health problems due to exposure to work environment risk factors. Previous research in this area has only examined a few factors within nurses’ work environments, and those factors were not conceptualized with the goal of improving workplace mental health. The purpose of this study is to identify the most important work environment predictors of nurse mental health using a comprehensive and theoretically grounded measure based on the National Standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…35 This is further evidenced by previous research with the standard that consistently found workload management, psychological protection, engagement, and physical safety as important determinants of nurse anxiety, depression, PTSD, burnout, and life satisfaction. 9 In light of these findings, future research should evaluate the mediating effect of nurse mental health on the relationship between GMW factors and quality and safe care provision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 This is further evidenced by previous research with the standard that consistently found workload management, psychological protection, engagement, and physical safety as important determinants of nurse anxiety, depression, PTSD, burnout, and life satisfaction. 9 In light of these findings, future research should evaluate the mediating effect of nurse mental health on the relationship between GMW factors and quality and safe care provision.…”
Section: Discussionmentioning
confidence: 99%
“…2 Furthermore, another recent study of the Standard has found that among the 13 workplace factors, workload management, worklife balance, and psychological protection were the most important determi-nants of nurse adverse mental health outcomes including depression, anxiety, and posttraumatic stress disorder (PTSD). 9 In recognition of the rising mental injury among nurses and other health care providers, BC health authorities were mandated in 2016 to implement the Standard to protect the mental health of their nursing workers and other health care providers in the workplace. 2 The implementation of the Standard begins with a comprehensive, baseline assessment of workplace conditions most important to employee mental health using the GMW survey.…”
mentioning
confidence: 99%